REINTEGRASI KONSEP MAQASHID SYARI’AH DALAM ADAT BASANDI SYARA’, SYARA’ BASANDI KITABULLAH - Wimra, Zelfeni (JURIS (Jurnal Ilmiah Syariah), 2016)
This article discusses the concept of reintegration in the implementation maqashid sharia of the customary law: Adat Basandi Syara', Syara' basandi Kitabullah (ABSSBK) in Minangkabau cultural region. This paper provides a scientific answer, how it should be, in practice, maqashid sharia as an integral part in ABSSBK. To collect, to analyze, and to interpret the data comparative literature was used. The basic values were compared with the concept of maqashid sharia ABSSBK. The result showed that the terms of syara’ found in the philosophy of ABSSBK have the similar characteristics to maqashid sharia, yet the device has not formulated detailed practicesl. The implications and significance showed clear link between the value (axiology) syara and maqashid sharia. Therefore, maqashid sharia can be referred in establishing ABSSBK as a basis of thought, movement and arbitration of nation-state.